The capital-labor relationship in Industry 4.0 - Foladori, Guillermo (2022)
The term industry 4.0 is present in academia, the business sector, and the media. It is associated with a new technological revolution characterized by the interrelation of various technologies, whose main elements are cyber-physical systems, artificial intelligence, and global connectivity. Although there is abundant literature on the subject, most of it is oriented from a technical and business perspective, and it is optimistic in terms of expected advantages. However, this article analyzes the potential for altering the traditional terms of the contradictory capital-labor relationship. Through an extensive literature review, industry 4.0 is described in its historical-economic context, highlighting the trends it drives. While most authors emphasize connectivity and technical interaction, this text emphasizes the distinctive economic aspect of this revolution. It highlights how the involvement of disruptive technologies to achieve high automation represents a clear trend towards the disappearance of salaried employment, with the exception of the minimal occupation of skilled labor and services. The union of this type of technologies represents a qualitative leap due to the elimination of downtime between individual companies and along all production chains. It concludes by showing the radical alteration in labor relations if industry 4.0 expands.